EFEKTIVITAS PELAYANAN PROGRAM KARTU PELAKU USAHA KELAUTAN DAN PERIKANAN (KUSUKA) PADA DINAS PERIKANAN KOTA KENDARI - Muh. Amir; Asriani Asriani; Muhamad Adin (Journal Publicuho, 2022)
This study is aimed at knowing the effectiveness of card programs KUSUKA at the Kendari City Fisheries Service Office this research is a qualitative, by using aqualitative descriptive research method. Data collection techniques and documentary studies. Analysed using Miles and Huberman’s method. The effectiveness of the Kusuka Card Program Service at the Kendari City Fisheries Office views of the five research indicators are well. Where, from the aspect of understanding the program is seen that The percentage of the Kusuka Card Program understanding by the Fisheries Service employees can be said to be very good. Similarly, the goal of the accuracy of the target, where the processing of data candidates of the Kusuka Cardiac data is carried out through a strict and integrated process with ministry data so that the channel of the Kusuka Card program can reach the parties who are truly a qualified fishery business personnel. But even so, there is still an indication of human error in the registry process that some societies are listed as fishermen but have actually switched other professions. According to the punctuality of the time, it is evident that although there is no clear rule of service time, the card service process I like is fast-tracked to be completed in less than 24 hours as long as the registry data is valid in the ministry.  In addition, in terms of exposure to the objectives and the existence of real changes, it is seen that the perpetrators of the fishery business that has had the Kusuka Card has benefited in the form of the process of insurance claims and the help of fishery infrastructure facilities.